IDENTITY ALIENATION AND CORRUPTION IN NORTH AFRICAN SOCIETIES - Mounir Hafid; Abdellatif Bouroubi; Zedira Khammar (International Journal of Innovative Technologies in Social Science, 2025)
This article discusses how identity alienation and corruption interact in North African societies, leading to negative consequences. Identity alienation causes individuals to feel disconnected from their community, diminishing their sense of belonging and public interest. This detachment can foster a sense of excessive self-esteem, resulting in moral corruption and exploitation of one's position for personal gain. The interplay between these two phenomena exacerbates corruption, as alienated individuals may prioritize personal goals over societal well-being. The text emphasizes the need to explore the relationship between identity alienation and corruption to develop long-term strategies for combating corruption by addressing the underlying issues that contribute to its spread.